1997
DOI: 10.1136/ard.56.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Increase of HLA-DRB1*0408 and -DQB1*0301 in HLA-B27 positive reactive arthritis

Abstract: Objective-To study HLA class II association in reactive arthritis. Methods-63 patients with reactive arthritis and 46 with rheumatoid arthritis were included in the study. HLA-DR alleles were determined by using a sequence specific PCR method. Oligonucleotide hybridisation was used for definition of DRB1*04 subtypes and DQB1 alleles. HLA-B27 was determined by standard microcytotoxity test or by PCR. HLA-B27 subtyping was made by sequencing. Results-46 (73%) of 63 patients with reactive arthritis were HLA-B27 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
1
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
5
10
1
1
Order By: Relevance
“…In addition to the HLA-DR4 subtypes *0401, *0404 and *0408 the subtype *0405 belongs to those so called RA risk alleles. It, however, is very rare in the healthy Finnish population42 and we could not find any DRB1*0405 positive persons either in the familial or the non-familial group. The increased frequency of DR4 in familial RA patients was also reflected in the higher amount of so called SE in them.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…In addition to the HLA-DR4 subtypes *0401, *0404 and *0408 the subtype *0405 belongs to those so called RA risk alleles. It, however, is very rare in the healthy Finnish population42 and we could not find any DRB1*0405 positive persons either in the familial or the non-familial group. The increased frequency of DR4 in familial RA patients was also reflected in the higher amount of so called SE in them.…”
Section: Discussioncontrasting
confidence: 73%
“…There were only four (3.1%) patients in the familial and eight (3.7%) patients in the non-familial group with that allele combination. HLA-DRB1*0401 and *0404 are the two common subtypes in our population42 and these known RA associated HLA-DR4 subtypes were found in equal frequencies in both our familial and non-familial RA groups, the subtype *0401 was more frequent than *0404 in both study groups. McDonagh and coworkers found a relatively high prevalence of DRB1*0408 (16.7%) in their familial RA patients (no non-familial patients) and suggested the possibility that the DRB1*0408 allele may have a more important role in familial RA 43.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…35 DQB1*0301 has also been reported in association with the closely related disorder BP, in which circulating autoantibodies target similar BMZ antigens. 16,36 Sarcoidosis has been associated with DQB1*0301-bearing haplotypes, 37 reactive arthritis with HLA-B27/ DRB1*0408/DQB1*0301, 38 alopecia areata with DRB1*1104 and DQB1*0301 39 and lichen sclerosus with DR4/DQ7. 40 In conclusion, our study confirms that the majority of patients with MMP share a common genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…Tuokko et al also showed an increased TNFc1 frequency in patients with reactive arthritis independently of HLA-B27 [5]. TNFc1 might also be a new susceptibility marker for reactive arthritis.…”
Section: Introductionmentioning
confidence: 91%